DMLS – An insight for unproblematic production. (2021) - Malladi, Avinash; Karunakaran, K.
Abstract: Three dimensional printing is a kind of production of things stratum by stratum deposition of material. It helps to cross many limitations to manufacture the product with desired features which are difficult to machine in subtractive manufacturing methods. At earlier stage of progress of three dimensional printing, objective of coming out with basic creation of some trial products, reduces the manufacturing time in reckoning. Current trend is with powder-based AM, where a part is manufactured with DMLS (Direct Metal Laser Sintering process) which helps to produce an end-use part. Every manufacturing process will be having some defects during the unorganized parameters. In this regard, this paper discusses about the complete procedure of DMLS and defects and the causing parameters to facilitate the trouble free and defect free manufacturing of parts. This papers also addresses the research scopes.